Human, All Too Human: Do We Lose Free Spirit in the Digital Age? - Aleksandra Sushchenko; Olena Yatsenko (Humanities)
This article engages in a philosophical dialogue with Nietzsche’s views on the discourse of power, examining the rising concerns surrounding the digitization and algorithmization of society in the context of advancements in robotics and AI. It highlights human agency through Nietzsche’s perspective on creative culture as a space for individuals to actively engage in free thought and action, with responsibility as the key foundation of social resilience. By approaching metaphysical systems through the discourse of power, Nietzsche emphasizes that humanity can overcome system-driven delusions through reason, which he understands as the form of critical reflection existing solely in the domain of creative culture. We assert that Nietzsche’s arguments offer alternative perspectives on the ethics of technology, particularly through the dialectics of “weak and strong types of behavior”. It allows us to explore how resistance—existing in creative culture—can serve as a vital counterbalance to the mechanization of social life. Such dialectics provide a strong foundation for supporting algorithmic resistance by inspiring ethical frameworks rooted in individuality and emotional depth, challenging the homogenizing tendencies of digitization and algorithmization. It emphasizes the importance of subjective stories, emotions, and compassion, forming human-centered ethical principles that preserve the richness of individual experiences and protect against system-driven delusions.